Effects of neurocognitive intervention in older adults. A systematic review - Elizabeth Jiménez Puig; Zoylen Fernández Fleites; Yunier Broche Pérez; Daniela Beatriz Vázquez Martínez (Medisur)
Background: The need for neurocognitive intervention in older adults, as well as the various positions regarding its benefits, justify the relevance of systematizing the dissimilar proposals for neurocognitive intervention in people with and without cognitive deficits. Knowledge of the impact of these interventions on the cognitive health of these people is vitally important. Objective: to describe, through a systematic review of the scientific literature, the effects of neurocognitive intervention on cognitive health in healthy older adults, and in older adults with mild cognitive impairment or dementia. Methods: a descriptive study was carried out, which consisted of a systematic review of the scientific literature on the subject; and started from the search in the databases: PubMed, PsycInfo, Scielo, Cochrane and EBSCO, from August to December 2018. The PRISMA Declaration was used. 426 articles were found. After applying the inclusion, exclusion and exit criteria, and analyzing the overlap effect, six articles made up the sample. Results: the main forms of neurocognitive intervention were stimulation and training. The most frequently used modality was neurocognitive stimulation. Effects of improvement in processing speed, selective attention, planning, reaction time, categorization, verbal fluency, comprehension, visual recognition and orientation were reported. Conclusion: The existing empirical evidence on the implementation of neurocognitive intervention programs during the last ten years points to paths towards effective intervention and improvement of the quality of life of adults.